Municipal water financing models and partnerships in South Africa - Mahomed, Yaseen (Graduate School of Business (GSB), 2023)
Water is necessary for both survival and development. Despite this, many individuals in South Africa lack access to safe and clean drinking water. In most developing countries, water provision is primarily the responsibility of the government. Given the current constrained environment and the significant challenge of increasing water provision, there is a case to be made for adopting various configurations, including more private sector involvement. Drinking water that is clean and safe is a global issue that affects both the public and private sectors. While South Africa has made progress in improving water services, it has been inconsistent, with a substantial percentage of the poor being unserved. Concerns about institutional and financial capability, infrastructure maintenance, apartheid-era spatial planning challenges, and corruption are just some of the challenges that South Africa faces. The researcher investigates the water service delivery models used in South African municipalities in this study. The study aims to answer the following question: “How do municipalities operating in a constrained environment, with limited capacity to enforce regulations, ensure adequate water provision for all its citizens?” The researcher posits that one way to answer this question, is to determine which model of water provision is best suited to South Africa. To better understand the theoretical and empirical considerations with various water configurations, the researcher starts off with an extensive literature review, looking at developed and developing nations and focuses on the South African context. In answering the main research question, the researcher undertakes a mixed method research strategy that incorporates both quantitative and qualitative data. The study shows that water service authorities with public-sector contracts outperform those with private-sector contracts. According to the study, publicly designed water service authorities outperform privately configured ones in terms of efficiency, financial sustainability, accessibility, affordability, and customer centricity. The key factors underpinning this performance include the degree of urbanisation, the ability to cross-subsidize, and the demography of the region. That said, the private sector's efficiency and financial discipline yielded improved performances in the privately configured Water Services Authorities. The main conclusion is that there is no one-size-fits-all approach. The study finds that a public configuration is better suited to expanding water service delivery in the South African context based on a performance scorecard adopted in the study. The sector's complexity as well as South Africa's diversity, necessitates a customized approach that incorporates fundamental elements from both configurations. 394 words Keywords: Water, water supply, configurations, public, private, efficiency, sustainability, accessibility, affordability